2017
DOI: 10.1093/jjco/hyx067
|View full text |Cite
|
Sign up to set email alerts
|

A Phase 1 study evaluating AMG 337 in Asian patients with advanced solid tumors†

Abstract: AMG 337, a selective small-molecule MET inhibitor, was evaluated in Asian patients with advanced solid tumors. Eligible patients orally self-administered AMG 337; the initial dose of 150 mg once daily (QD) was escalated to 300 mg QD (modified 3+3+3 design). Treatment continued until disease progression, intolerability, or death. The primary endpoint was adverse events (AEs) and clinical abnormalities defined as dose-limiting toxicities (DLTs). Secondary endpoints included other AEs, pharmacokinetics and tumor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…The association between MET amplification and a poor disease prognosis has likewise been confirmed in a meta-analysis (23). Beside the disease prognostic characteristics, it has been suggested that MET amplification potentially possesses predictive properties in relation to Met-targeted therapy and, thereby could act as a companion or complementary diagnostic in relation to the tyrosine kinase inhibitors under development for treatment of G/GEJ/E cancer and other indications (13,15,(24)(25)(26). Available data suggest that treatment plans targeting both Met and Her2 (human epidermal growth factor receptor 2 gene product) may be beneficial.…”
Section: Introductionmentioning
confidence: 83%
See 1 more Smart Citation
“…The association between MET amplification and a poor disease prognosis has likewise been confirmed in a meta-analysis (23). Beside the disease prognostic characteristics, it has been suggested that MET amplification potentially possesses predictive properties in relation to Met-targeted therapy and, thereby could act as a companion or complementary diagnostic in relation to the tyrosine kinase inhibitors under development for treatment of G/GEJ/E cancer and other indications (13,15,(24)(25)(26). Available data suggest that treatment plans targeting both Met and Her2 (human epidermal growth factor receptor 2 gene product) may be beneficial.…”
Section: Introductionmentioning
confidence: 83%
“…The study included 1,580 formalin-fixed and paraffinembedded (FFPE) G/GEJ/E adenocarcinoma specimens consecutively collected from the screening population of an international multi-center phase II trial with the Met tyrosine kinase inhibitor AMG337 (Amgen) (25). The limited demographic and clinical data were collected in relation with the MET eligibility testing for inclusion in the clinical phase II study with AMG337.…”
Section: Patients/specimensmentioning
confidence: 99%